PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPA SISWA KELAS III SEKOLAH DASAR - Utami, Sarwik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The purpose of this study is to improve student learning outcomes on the subject of “the characteristics andneeds of creature” the score obtained by students is still under the criteria of minimal Exhaustiveness that is 70.To achieve the score determined then the authors use the method of media images. This method involves a lot ofstudent activities. Subjects in this study were students of class III A Elementary School 017 Kundur. Datacollection procedures by using observation which contains teacher learning procedure consist of learningimprovement planning, teacher and student observation data and result of initial and final test. Data analysisuses qualitative data. This study was conducted in two cycles. Every cycle has planning, implementation,observation reflection and assessment. To see pre-cycle student learning outcomes. In pre-cycle, score obtainedfor the first complete one is 12 people (54,55%) not complete as many as 10 people (45,45%). The first cycle is15 people (72.73%) and not complete as many as 7 people (27.27%). Cycle II has completed totally 22 people(100%). For the range of score 80 - 89 and the criteria of high assessment. In conclusion, the use of imagemedia methods can improve the results and motivation of students' learning grade III A state elementary school017 Kundur.